GIG ECONOMY DAN PERLINDUNGAN PEKERJA PLATFORM: TINJAUAN HUKUM KEBIJAKAN EKONOMI TERHADAP SISTEM PENILAIAN KINERJA (RATING) DI INDONESIA - Nisrina Balqis Huwaida; Akhmad Farroh Hasan (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
The development of the digital economy in Indonesia has driven the emergence of the gig economy, characterized by the increasing use of app-based platforms across various sectors, including ride-hailing, delivery services, and household services. This transformation presents legal challenges, particularly concerning the status of the relationship between platform workers and application service companies, which is generally structured on a partnership model. Furthermore, legal protection for platform workers remains limited, especially with regard to the use of performance rating systems that directly affect workers' opportunities to obtain work, their income levels, and the continuity of their partnership arrangements. This study aims to examine the implications of rating systems for the protection of platform workers' rights from the perspective of economic policy law. The method employed is normative juridical research with a comparative approach, conducted through the analysis of legislation, platform policies, court decisions, as well as relevant literature and practices across several countries. The findings indicate that Indonesia's existing labor regulations have yet to adequately accommodate the distinctive characteristics of employment relationships within digital platform ecosystems. Moreover, the implementation of rating systems managed unilaterally by platform companies has the potential to create an imbalance in legal relationships, as such systems are not accompanied by clear and transparent contestation mechanisms. Accordingly, a dedicated policy framework is needed to govern platform worker protection, including restrictions on the use of ratings as a basis for imposing sanctions, and the establishment of a supervisory mechanism involving the government, platform companies, and workers, with a view to ensuring legal certainty and a fair balance of interests among all parties concerned.